Stock Identification of Short Mackerel (Rastrelliger brachysoma) in the Upper and Middle Gulf of Thailand by Morphological Characters - Kaewalee Viboonkit; Wimonmat Boonmee; Chayanin Thotsagotphairee; Piyada Tavitchasri; Thiamphop Kanloung (My University, 2023)
Rastrelliger brachysoma, a short mackerel, is a significant pelagic fish that is common in the fisheries in the Gulf of Thailand. The management of fish stocks is a prerequisite for fish conservation strategies and profitable fisheries. Morphological character differences between stocks of species provide a method for identifying fish stocks. This study was aimed to identify stock population of short mackerel in the Upper and Middle Gulf of Thailand. The fish specimens were collected from four different locations: Chonburi and Prachuap Khiri Khan (central provinces of Thailand), Chumphon and Surat Thani (southern provinces of Thailand). Twelve morphometric characters of fish were assessed to determine the stock populations by stepwise discriminant analysis. The results showed that 12 morphometric characters were significantly different among the four populations. In the discriminant function analysis, the first function explained 61.30% of total variations, whereas the 2nd and 3rd functions were 26.50% and 12.20%, respectively. The characters included total length, standard length, folk length, head length, post – orbital length, pre – dorsal length, pre – pelvic length, 1st dorsal to 2nd dorsal length, pelvic to anal length, pre – anal length, head depth, and greatest depth, all of which can be used to differentiate these populations. According to the results of the discriminant analysis, the populations of short mackerel were predicted and subsequently classified with an accuracy rate of 54.88%.
Keywords: Discriminant function analysis; Stock (firearms); Fish Biology and Ecology Studies